2010
DOI: 10.1590/s0034-71672010000200023
|View full text |Cite
|
Sign up to set email alerts
|

Foco no cliente: ferramenta essencial na gestão por competência em enfermagem

Abstract: Reflection about a doctorate's thesis. It was carried through an abstraction of the described theory by specialist authors in thematic, a transposition for the practical of competency management in nursing. The essential competency shows attributes of knowledge, ability and attitude - called CHA, to add value to the organization of health with focus in the customer. It is essential to awake in all the team, the responsibility and real concern with the patient, family and visitors. The professional constitutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 2 publications
0
5
0
5
Order By: Relevance
“…In the Patients' participation perspective the contributions cluster around the concepts autonomy 21,[24][25][26]30 , self-care 12,19,21,22,29,31 , valuing experience 20,23 and patients' participation 13,21,28,32 .…”
Section: National Contributions On Pccmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Patients' participation perspective the contributions cluster around the concepts autonomy 21,[24][25][26]30 , self-care 12,19,21,22,29,31 , valuing experience 20,23 and patients' participation 13,21,28,32 .…”
Section: National Contributions On Pccmentioning
confidence: 99%
“…These studies focused on PCC in connection with the following aspects: 1) Enlarged healthcare perspective, 2) Patients' participation in care and 3) Humane care. In regard to the Enlargement of the healthcare perspective there is a cluster of contributions on holistic care 13,[19][20][21][22][23][24][25][26] , comprehensive care 13,20,[24][25][26][27][28] and health needs oriented care 13,19,21,22,24,25,28,29 .In the Patients' participation perspective the contributions cluster around the concepts autonomy 21,[24][25][26]30 , self-care 12,19,21,22,29,31 , valuing experience 20,23 and patients' participation 13,21,28,32 .Patients' participation in care is defined as an opportunity for the exercise of citizens' rights in the quest for autonomy (related to ideas of freedom, leading role, COMUNICAÇÃO SAÚDE EDUCAÇÃO 2016; 20(59):905-16 respect for subjectivity 33 as an important condition for self-care 19,20,33 . The concept of self-care is understood as a way of managing the healthcare process, implying the collaboration of the health te...…”
mentioning
confidence: 99%
“…In this understanding, hospital organizations need to understand that assessing satisfaction and listening to complaints are the most effective means for clients to provide ways to improve the care provided. 24 Assessing client service and satisfaction, similar to companies in other segments that need to retain their clients, should be valued in healthcare organizations because they provide and sell complex services that, in most cases, the client spontaneously would not like to receive or are undesirable due to illness, need for recovery of their health or maintenance of life. 3 In this aspect, it can be inferred that even if they do not wish to return to the hospital, the satisfied client is a source of referral to other clients and to the positive image of the organization thus highlighting its social mission in the health system.…”
Section: Discussionmentioning
confidence: 99%
“…26 Customer satisfaction is part of quality standards in all processes and services offered and must meet and exceed their desires or enchant them. 24 Studies that assessed satisfaction in public service attendance found fragility of humanization of care due to deficiencies in reception and communication, contributing to client dissatisfaction. 14,15,22 Thus, it was evident that the client's wishes, which are considered obvious or even elementary, should not be neglected, since the non-fulfillment of these wishes may trigger dissatisfaction and compromise the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…This research shows that nurses coordinate the NSP in half the studied institutions. Multidisciplinary work in risk management is unrestricted, although studies show nurses are one of the most active workers in this sector (10) . Ideally, however, NSPs should be structured according to the prior experience of health workers in patient safety and quality and linked to the hospital infection control committee, risk management, nursing, quality, and other sectors (3) .…”
Section: Discussionmentioning
confidence: 99%